IDENTIFIKASI HAMBATAN PELAKSANAAN PRAKTIKUM BIOLOGI DAN ALTERNATIF SOLUSINYA DI SMA NEGERI 1 MOGA : - - Masruri Masruri (Perspektif Pendidikan dan Keguruan, 2020)
This study aims to determine the barriers to carrying out practical activities and find alternative solutions that can overcome them through a literature review. The method used is the survey method and literature review. Laboratory survey results, student opinions, and teacher opinions show that obstacles in carrying out practical activities include the lack of laboratory facilities, the lack of supporting facilities and infrastructure, the absence of laboratory assistants, insufficient time allocation. An alternative solution that teachers can do is to use a virtual laboratory. Virtual practicum is a series of laboratory tools in the form of interactive multimedia-based computer software, which is operated by a computer and can simulate activities in the laboratory as if the user were in a real laboratory. Therefore, virtual practicum as a product of technological progress can be an alternative solution to overcome these obstacles.